Swedish parents’ interest in preconception genetic carrier screening - Ekstrand Ragnar, Maria ; 0000-0003-4735-6162; Tydén, Tanja; Kihlbom, Ulrik; Larsson, Margareta (Upsala Journal of Medical Sciences, 2016)
Introduction: Genetic technologies advance rapidly. It is possible to undergo genetic carrier screening before pregnancy to examine genetic risks to future offspring. We aimed to investigate parents’ interest and motives towards preconception genetic carrier screening (PCS) as well as factors associated with interest in PCS. Material and methods: Our study sample consists of 777 parent couples within the longitudinal Swedish Pregnancy Planning study. Women responded to questionnaires at three occasions: in early pregnancy, late pregnancy, and one year after childbirth. Male partners responded to one questionnaire one year after childbirth. Results: One-third of the parents were positive (30% versus 34% of women and men, respectively), less than a third were negative (26% versus 28%), and 45% versus 38% were uncertain about whether to consider PCS before a future pregnancy. No differences in PCS interest were found between women and men (P = 0.091), but a higher proportion of women were concerned about negative consequences (53% versus 46%, P < 0.003) and were ‘opposed to such a way of child selection’ (31.8% versus 25.2%, P = 0.002). Factors associated with PCS interest were experiences of prenatal diagnostics and positive attitudes towards finding out or choosing sex of one’s child (women), and prenatal diagnostics, self-rated poor health, and pregnancy planning (men). Conclusion: Both women and men had relatively high uncertainty towards PCS, but women were more concerned about negative consequences. The future extent of the clinical utility of PCS is currently unknown, but parents’ interests and doubts are important aspects to consider. © 2016 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Interest; motives; parents; preconception genetic carrier screening